Early Medieval Hagiography - Palmer, James T. (James Trevor) (Past imperfect (ARC Humanities Press), 2018)
Saints were powerful role models in the early Middle Ages, capable of defining communities. But what roles did saintly biographies play in shaping the medieval West? Can we understand society and its many post-Roman transformations through them? This short book takes readers from the creation of medieval hagiography, through the ways in which it circulated, to a wide-ranging assessment of different modern methodologies used to interrogate hagiographies, from early twentieth-century source criticism, to the insights gained from gender studies, postmodernism and digital humanities.